2008
DOI: 10.1093/ajcn/87.4.1019
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of a common single-nucleotide polymorphism (GPX4c718t) in the glutathione peroxidase 4 gene: interaction with sex

Abstract: Background: Selenium is essential for health in humans. Selenium is present as selenocysteine in selenoproteins such as the glutathione peroxidases (GPx). Selenocysteine incorporation requires specific structures in the 3Јuntranslated region (3ЈUTR) of selenoprotein mRNAs. Objective: This study investigated the functional significance of the single-nucleotide polymorphism (SNP) GPx4c718t within the 3ЈUTR of the GPx4 gene. Design: A selenium supplementation trial was carried out with prospectively genotyped ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
2
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 43 publications
5
109
2
6
Order By: Relevance
“…In Europe, a relatively low Se status comparable with that in the bottom tertile of the NPC study is common (9), suggesting that Se supplementation could elicit some prostate cancer protection in European men. In addition, recent data not only indicate that genetic variations in selenoprotein genes account for interindividual differences in response to Se supplementation (10,11) but also that they may influence cancer risk (12,13). Such observations may help to reconcile the complex observations from both the NPC and SELECT studies and also identify subgroups of the population at increased or decreased risk of prostate cancer depending on their Se status and capacity to respond to Se intake.…”
Section: Introductionmentioning
confidence: 96%
“…In Europe, a relatively low Se status comparable with that in the bottom tertile of the NPC study is common (9), suggesting that Se supplementation could elicit some prostate cancer protection in European men. In addition, recent data not only indicate that genetic variations in selenoprotein genes account for interindividual differences in response to Se supplementation (10,11) but also that they may influence cancer risk (12,13). Such observations may help to reconcile the complex observations from both the NPC and SELECT studies and also identify subgroups of the population at increased or decreased risk of prostate cancer depending on their Se status and capacity to respond to Se intake.…”
Section: Introductionmentioning
confidence: 96%
“…For example, rs1050450 causes a Pro-Leu amino acid change in glutathione peroxidise 1 and affects protein function [12], rs713041 causes a T-C substitution in a region of the glutathione peroxidise 4 (GPX4) gene corresponding to the 3 0 UTR of the mRNA and alters the protein binding to the 3 0 UTR and reporter gene activity [3,21], rs5859 and rs5845 in the 3 0 UTR of the 15-kDa selenoprotein affect reporter gene activity [13] and rs7579 and rs3877899 in the SEPP1 gene affect biomarkers of selenoprotein status in vivo [20]. Variants in the promoter of SELS are functional in that they modulate SelS expression and plasma levels of inflammatory cytokines [10].…”
Section: Introductionmentioning
confidence: 99%
“…Gautrey with coworkers 23 have shown that the C718T variant of the GPX4 gene alters the pattern of selenoprotein synthesis under low selenium intake. Méplan with coworkers 15 have observed that carriers of the genotype 718CC maintain GPX4 concentrations better than carriers of genotype 718TT do when selenium intake falls after withdrawal of the selenium supplement. Interestingly, the authors have also showed that the polymorphism influences the expression of other selenoproteins such as GPX1 and GPX3.…”
Section: Biological Role and Functional Studies Of The Gpx4 Genementioning
confidence: 98%
“…15 The gene for glutathione peroxidase-4 is expressed in most tissues, including the brain (Gene Expression Atlas, available at http://www.ebi.ac.uk/gxa/gene/ ENSG00000167468). Although the GPX4 gene is highly polymorphic, a limited number of studies [16][17][18][19] have been done to investigate genetic variations within the GPX4 gene that could potentially alter the function of the enzyme.…”
Section: Biological Role and Functional Studies Of The Gpx4 Genementioning
confidence: 99%
See 1 more Smart Citation